PEMBATALAN PERIKATAN PERJANJIAN JUAL-BELI TANAH SECARA SEPIHAK OLEH PENJUAL YANG SUDAH DILAKUKAN PEMBAYARAN SECARA BERTAHAP - Muhammad Japri; Sitti Aisyah; Maria Ana Liwa; Aji Titin Roswitha Nursanthy (Collegium Studiosum Journal, 2026)
An agreement to purchase land creates rights and responsibilities for both parties. The seller has the obligation to deliver the land, while the buyer must pay the agreed amount. In practice, sellers often unilaterally cancel land purchase agreements, even though the buyer has made installment payments. This situation raises legal issues regarding legal certainty, protection for good-faith buyers, and the application of the principle of pacta sunt servanda in contract law. This study aims to analyze whether the cancellation of a land purchase agreement by the seller after installment payments have been made is legally valid, as well as to examine the legal consequences for both parties. The method used is normative legal research with a statutory approach and a conceptual approach, analyzing the Civil Code, relevant land regulations, as well as related theories and court decisions. The results of the study indicate that if a seller cancels a land purchase agreement without a valid reason based on the contract or the law, such action is impermissible. This cancellation can be considered a breach of contract (wanprestasi), requiring the seller to pay damages and granting the buyer the right to demand the execution of the agreement or its cancellation through a court decision. Therefore, it is crucial to provide legal protection to buyers who have paid in installments to ensure legal certainty and justice for all parties.